Rapamycin protects against neuronal death and improves neurological function with modulation of microglia after experimental intracerebral hemorrhage in rats - Li, D; Liu, F; Yang, T; Jin, T; Zhang, H; Luo, X; Wang, M (Cellular and Molecular Biology, 2016)
Intracerebral hemorrhage (ICH) results in a devastating brain disorder with high mortality and poor prognosis and effective therapeutic intervention for the disease remains a challenge at present. The present study investigated the neuroprotective effects of rapamycin on ICH-induced brain damage and the possible involvement of activated microglia. ICH was induced in rats by injection of type IV collagenase into striatum. Different dose of rapamycin was systemically administrated by intraperitoneal injection beginning at 1 h after ICH induction. Western blot analysis showed that ICH led to a long-lasting increase of phosphorylated mTOR and this hyperactivation of mTOR was reduced by systemic administration of rapamycin. Rapamycin treatment significantly improved the sensorimotor deficits induced by ICH, and attenuated ICH-induced brain edema formation as well as lesion volume. Nissl and Fluoro-Jade C staining demonstrated that administration with rapamycin remarkably decreased neuronal death surrounding the hematoma at 7 d after ICH insult. ELISA and real-time quantitative PCR demonstrated that rapamycin inhibited ICH-induced excessive expression of TNF-Î± and IL-1Î² in ipsilateral hemisphere. Furthermore, activation of microglia induced by ICH was significantly suppressed by rapamycin administration. These data indicated that treatment of rapamycin following ICH decreased the brain injuries and neuronal death at the peri-hematoma striatum, and increased neurological function, which associated with reduced the levels of proinflammatory cytokines and activated microglia. The results provide novel insight into the neuroprotective therapeutic strategy of rapamycin for ICH insult, which possibly involving the regulation of microglial activation.